Evaluation of emerging additive technologies for circuit board manufacturing - Almquist, Gustaf (My University, 2019)
This thesis is focused on introduction of the state-of-the-art additive manufacturing process for circuit board manufacturing in the development process. Project was carried out at Saab AB during 2018 and is done in collaboration with the department for Industrial and Materials Science at Chalmers. Focus of the thesis is to evaluate the possibilities and limitations of the recently developed manufacturing technology, that allows for additive manufacturing of a Printed Circuit Board (PCB). The technology was developed and launched by Nano Dimensions Ltd in the autumn of 2017. The additive manufacturing technology used is based on modified material jetting process that utilizes an ink containing silver or copper nano-powder in one printing head, and dielectric ink in other. This allows for simultaneous printing of both materials. After printing, green part is cured at elevated temperature in order to sinter metal nano-powder and cure dielectric material. This is done by exposure to light from a photonic curing lamp after each layer is deposited. This allows to produce complex two- and three- dimensional circuit boards, providing the possibility to significantly speed-up process of PCBs development and prototyping. It also allows for manufacturing 3D PCBs, not possible with the conventional technologies. Focus is on the evaluation of the performance of the PCBs, made by new technology, extensive characterisation of the microstructure of the PCBs, as well as defects and flaws that can affect its applicability. The results were used to estimate applicability of this technology at Saab. Product Lifecycle (PLC) for the PCBs made by this technology was evaluated as well. Thesis also covers development of a method for evaluation of the new processes for PCB development following lean testing and qualitative methodology. While including stakeholders in the process and managing risks, it also discusses current state of additive manufacturing of electronics. For this purpose, an evaluation board was developed and printed using the new process. Unfortunately, the board broke during assembly, but material testing and inspections have given insights into the current state of PCB 3D-Printing. Additive manufacturing of circuits and especially PCBs stand to develop rapidly over the coming years. Even at their current stage they allow to speed up development and allow for quick production of small series for production. Current limitations in additive processes limits its implementations but allows for rapid prototyping of low- to mid- frequency circuits. The technology shows promising results and potential to remove logistic bottlenecks, reduce waste and reduce the need for end of life purchase of components.
Keywords: Materialvetenskap; Produktion; Materialteknik; Materials Science; Production; Materials Engineering